Differences in Processing and Presentation of Indonesian Food in America and Indonesia - Gunawan, Steven; Lis Indrianto, Agoes Tinus (Stupa, 2021)
A fine food is a food that represent itself where it came from even those food is made far away from original place. Originality of food remain consistent while the taste and presentation may deliberately change to fit the culture and personal habit of the original citizen. The main objectives of this study are to recognize and describe the different process and presentation of Indonesian food that has been made in two specific different countries, Indonesia dan America. This research was conducted through textual analysis and qualitative data collection namely by personal observations, interviews, and documentations. This research observes the cultural and habitual action of the people who lived in Indonesia and America. The findings show variation in the aspect of processing and presenting Indonesia food in Indonesian and American context. The same food and ingredients may be different in the presentation and processing based on the cultural background of the place where the food is produced. Although this research analyzes specific context of places, but essence of culture that affect the food presentation and processing can be applied in any regions and culture.